Comparing radiographic scores for prediction of complications and outcome of aneurysmal subarachnoid hemorrhage: Which performs best?. (29th November 2022) - Said, Maryam; Odensass, Svenja; Gümüs, Meltem; Rodemerk, Jan; Chihi, Mehdi; Rauschenbach, Laurèl; Dinger, Thiemo Florin; Darkwah Oppong, Marvin; Dammann, Philipp; Wrede, Karsten Henning; Sure, Ulrich; Jabbarli, Ramazan
Abstract: Background and purpose: Aneurysmal subarachnoid hemorrhage (aSAH) is characterized by high morbidity and mortality proceeding from the initial severity and following complications of aSAH. Various scores have been developed to predict these risks. We aimed to analyze the clinical value of different radiographic scores for prognostication of aSAH outcome. Methods: Initial computed tomography scans (≤48 h after ictus) of 745 aSAH cases treated between January 2003 and June 2016 were reviewed with regard to Subarachnoid Hemorrhage Early Brain Edema Score (SEBES), and Claassen, Barrow Neurological Institute (BNI), Hijdra, original Graeb and Fisher scale scores. The primary endpoints were development of delayed cerebral ischemia (DCI), in‐hospital mortality and unfavorable outcome (modified Rankin Scale score >3) at 6 months after subarachnoid hemorrhage. Secondary endpoints included the different complications that can occur during aSAH. Clinically relevant cutoffs were defined using receiver‐operating characteristic curves. The radiographic scores with the highest values for area under the curve (AUC) were included in the final multivariate analysis. Results: The Hijdra sum score had the most accurate predictive value and independent associations with all primary endpoints: DCI (AUC 0.678, adjusted odds ratio [aOR] 2.83; p  < 0.0001); in‐hospital mortality (AUC 0.704, aOR 2.83; p  < 0.0001) and unfavorable outcome (AUC 0.726, aOR 2.91; p  < 0.0001). Multivariate analyses confirmed the independent predictive value of the radiographic scales for risk of decompressive craniectomy (SEBES and Fisher score), cerebral vasospasm (SEBES, BNI score and Fisher score) and shunt dependency (Hijdra ventricle score and Fisher score) after aSAH. Conclusions: Initial radiographic severity of aSAH was independently associated with occurrence of different complications during aSAH and the final outcome. The Hijdra sum score showed the highest diagnostic accuracy and robust predictive value for early detection of risk of DCI, in‐hospital mortality and unfavorable outcome after aSAH.